What kind of social protection for what kind of democracy? Dilemmas of social inclusion in Latin America - Sonia Fleury (Social Medicine Publication Group, 2024)
It is very moving to be part of this celebration of 25th anniversary of ALAMES, the Latin American Association of Social Medicine. These many years have been filled with dreams, struggles, warmth and emotion, debates, disappointments. and hopes. Over this time we have aged and some of our dearest colleagues have passed away. Others left us. At times we grew disheartened; at others we were unable to see beyond our dogmatic positions and understand the need for change. But we regrouped, caught up with what was going on in the world, learned new things, added new partners, and built new strategies. Our vitality arises from the very choices that define the field of social medicine. Collective Health (as it is called in its Brazilian version) examines the interrelation between the biological and social orders, in other words, the concrete, historical associations of social determinants which affect living beings and how they relate to each other. We see the "social" as a field of inquiry which combines knowledge and action, both the study and practice of social transformation.